2021
DOI: 10.1002/uog.22171
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of automated three‐dimensional ultrasound imaging technique for fetal head biometry

Abstract: Automated three-dimensional ultrasound imaging using artificial intelligence can reliably identify and measure fetal biparietal diameter and head circumference, but is less consistent in accurately identifying and measuring transcerebellar diameter, cisterna magna and posterior horn of the lateral ventricle. What are the clinical implications of this work?Further optimization of this automated ultrasound imaging technology for fetal head biometry based on machine learning is necessary prior to incorporation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Nevertheless, manual navigation through brain volume datasets to retrieve differently oriented diagnostic planes along the x-, y-, and z-axes necessitates a comprehensive understanding of fetal CNS architecture and a spatial sense of anatomic relations and hence is highly operator dependent, especially when CNS abnormalities are suspected. It has recently been shown that automated volumetric approaches e ciently enable rapid and standardized evaluation of the fetal brain in terms of basic examination [41][42][43] or reconstruction of an entire neurosonogram. [12][13][14] By simplifying the evaluation process of basic and/or advanced CNS examination, these algorithms might aid in earlier detection of abnormal CNS anatomy in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, manual navigation through brain volume datasets to retrieve differently oriented diagnostic planes along the x-, y-, and z-axes necessitates a comprehensive understanding of fetal CNS architecture and a spatial sense of anatomic relations and hence is highly operator dependent, especially when CNS abnormalities are suspected. It has recently been shown that automated volumetric approaches e ciently enable rapid and standardized evaluation of the fetal brain in terms of basic examination [41][42][43] or reconstruction of an entire neurosonogram. [12][13][14] By simplifying the evaluation process of basic and/or advanced CNS examination, these algorithms might aid in earlier detection of abnormal CNS anatomy in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Common measurement items included fetal lateral ventricles, transcerebellar, cisterna magna, and posterior horn of the lateral ventricle, etc. (19,20). The methods were not very different from those of neonates, except for the image quality (the fetal head was further from the ultrasound probe, and sheltered by adjacent tissue or anatomical structures) and the difficulties of location caused by the fetal activity.…”
Section: Automatic Segmentation Of Fetal Head and Its Internal Structurementioning
confidence: 98%
“…In other recent research papers in our field, algorithms have been shown to be useful in identifying the fetal occiput position during labor 8 and in the classification of ovarian tumors as benign or malignant 9 . Additionally, major ultrasound machine manufacturers have unveiled applications that are based on algorithms, although their development and validity often remain unreported for commercial reasons [10][11][12] . Therefore, all of these AI systems should remain at Level 2 of automation (Figure 2) until robust clinical evidence is collected via prospective trials.…”
Section: Drukkermentioning
confidence: 99%